Analysis of Factors Influencing Green Motivation in South Jakarta MSMEs - Febrian, Wenny Desty; Solihin, Agung (International Journal of Psychology and Health Science, 2024)
The article Analysis of Factors Affecting Green Motivation in South Jakarta MSMEs is a literature review scientific article within the scope of marketing management science and social sciences. The purpose of this writing is to build a hypothesis of influence between variables which can later be used for further research within the scope of marketing management science and social sciences. The research method used is descriptive qualitative. Data was obtained from previous studies relevant to this research and sourced from academic online media such as publish or perish, google scholar, garba digital reference and jurnal sinta. The results of this article are: 1) Social support and education influence Micro, Small and Medium Enterprises in South Jakarta; 2) Market trends influence influence Micro, Small and Medium Enterprises in South Jakarta; and 3) Consumer preferences influence influence Micro, Small and Medium Enterprises in South Jakarta.